Deus sine nomine: Dialectic as a Tool for the Christian Interpretation of Boethius’s Consolatio III, m. 9, by Adalbold of Utrecht - Marek Otisk (Religions, 2023)
The Consolation of Philosophy by Boethius was not only widely read during the Middle Ages, but it was also frequently glossed, commented on, and discussed. The ninth poem of the third book, which offers a Platonic image of the creation of the cosmos and the governance over it, had a specific place in the reception of this Boethius’s work. Today we know of numerous debates about the possible interpretations of this poem and its Christian understanding, dating back at least to the 9th century. This paper deals with the commentary on this poem written by Adalbold of Utrecht († 1026). Attention is focused in particular on the role of dialectic in selected passages of this Adalbold’s text and on the inspirational sources of his dialectical knowledge. Specifically, the paper deals with the possibility of definition or description of God (Deus sine nomine), and arguments explaining the appropriateness or inappropriateness of conceptualizing God as the form of the highest good (forma summi boni).